A dominant role for chemoattractant receptor-homologous molecule expressed on T helper type 2 (Th2) cells (CRTH2) in mediating chemotaxis of CRTH2+ CD4+ Th2 lymphocytes in response to mast cell supernatants. - Gyles, S; Xue, L; Townsend, E; Wettey, F; Pettipher, R (2006)
Human cultured mast cells, immunologically activated with immunoglobuin E (IgE)/anti-IgE, released a factor(s) that promoted chemotaxis of human CRTH2+ CD4+ T helper type 2 (Th2) lymphocytes. Mast cell supernatants collected at 20 min, 1 hr, 2 hr and 4 hr after activation caused a concentration-dependent increase in the migration of Th2 cells. The effect of submaximal dilutions of mast-cell-conditioned media was inhibited in a dose-dependent manner by ramatroban (IC50 = 96 nm), a dual antagonist of both the thromboxane-like prostanoid (TP) receptor and the chemoattractant receptor-homologous molecule expressed on Th2 cells (CRTH2), but not by the selective TP antagonist SQ29548, implicating CRTH2 in mediating the chemotactic response of these Th2 cells. The effect of mast-cell-conditioned media was mimicked by prostaglandin D2 (PGD2) and this eicosanoid was detected in the conditioned media from activated mast cells in concentrations sufficient to account for the activity of the mast cell supernatants. Treatment of the mast cells with the cyclo-oxygenase inhibitor diclofenac (10 microm) inhibited both the production of PGD2 and the CRTH2+ CD4+ Th2-stimulatory activity, while addition of exogenous PGD2 to conditioned media from diclofenac-treated mast cells restored the ability of the supernatants to promote chemotaxis of these Th2 cells. The degree of inhibition caused by diclofenac treatment of the mast cells was concordant with the degree of inhibition of chemotactic responses afforded by CRTH2 blockade. These data suggest that PGD2, or closely related metabolites of arachidonic acid, produced from mast cells may play a central role in the activation of CRTH2+ CD4+ Th2 lymphocytes through a CRTH2-dependent mechanism.